The Different Clinical Aspects of Pediatric Primary Airway Tumors in the Larynx, Trachea, and Bronchi - Cho, Hyun-Ju; Yoon, Jisun; Lee, Eun; Lee, Yoon Se; Kim, Sang Yoon; Roh, Jong Lyel; Kim, Dong Kwan; Choi, Se Hoon; Park, Seung-Il; Kim, Yong-Hee; Koh, Kyung-Nam; Im, Ho Joon; et al. (Journal of Korean medical science, 2017)
Primary airway tumors are rare in children and no literature reviewed their characteristics each location. We evaluate the clinical characteristics and outcomes of Korean children with primary airway tumors, from the larynx to bronchi. A retrospective chart review of children with primary tumors of the larynx, trachea, and bronchi at Asan Medical Center from January 2000 to July 2016 was conducted. Nineteen children were diagnosed with primary airway tumors of the larynx (47.4%), trachea (10.5%), and bronchi (42.1%). Median follow-up duration was 2.8 years and there were recurrences in 21.1%. Laryngeal tumors were associated with a younger median age at onset (2 months) and diagnosis (4 months), and most were relatively small (median size = 5.3 mm) and symptomatic. Tracheal and bronchial tumors were found in older children (age at onset and diagnosis > 11 years) and large (> 15.0 mm). Most (75%) patients with bronchial tumors were asymptomatic and all the patients with tracheal tumors were symptomatic. This study suggests that we should consider different the locations in primary airway tumor based on the age at onset and diagnosis, initial symptoms or signs, and size of tumor.